Healthy Breakfast Education to Prevent Anemia in Elementary School Children using PowerPoint Media - Gilang Risma Aprilianti; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2022)
This study aims to educate about the importance of a healthy breakfast to prevent anemia in elementary school children. The study was conducted on 28 fourth-grade students at Hanjuang Samijaya Elementary School, Cihanjuang Village, Parongpong District, West Bandung, Indonesia. The method used is a quantitative research method with a pre-experimental design type one group pretest-posttest. The results showed that the average value of the pretest was 77.86 and the posttest was 89.29. The results of the comparison between the pretest and posttest showed an increase in respondents' knowledge after taking action in the form of education on the importance of having a healthy breakfast by consuming nutritious food. It is known that the average calculation result of N-Gain (Normalized Gain) is 58% (N-Gain > 40-55%). These results indicate that education about healthy breakfast is quite effective for elementary school students. This is indicated by the pretest score which is quite good, so students can know the importance of a healthy breakfast to prevent anemia. As for the results of the t-test calculation, it is known that T count (-8.132) < T table (1.703). That is, the students' post-test scores did not increase significantly. With the completion of this research, it is hoped that more students will know the importance of a healthy breakfast in an effort to prevent anemia.